B7-H1 Influences the Accumulation of Virus-Specific Tissue Resident Memory T Cells in the Central Nervous System - Pavelko, Kevin D.; Bell, Michael P.; Harrington, Susan M.; Dong, Haidong (Frontiers in Immunology, 2017)
Therapies that target the PD-1/B7-H1 axis have revolutionized cancer treatment, yet precise knowledge of how this pathway provides benefit continues to evolve. Here, we report a novel role for the immune checkpoint ligand B7-H1 in the accumulation of tissue-resident memory CD8+ T-cells (TRM). After intracranial infection, Theiler’s murine encephalomyelitis virus (TMEV) generates TRM that are maintained in the central nervous system (CNS) tissues of B7-H1WT animals. Although no differences in acute T-cell responses between B7-H1WT and B7-H1KO are observed, at long-term periods post-infection the maintenance of CD8+ TRM is diminished in B7-H1KO animals. This is accompanied by redistribution of the resident CD8+ population from primarily CD103+ TRM to a diminished population of TRM and a preponderance of non-specified PD-1+ CD103- CD8+ T-cells. T-cell transfer studies demonstrate that host B7-H1 is necessary for maintaining TRM and limiting accumulation of PD-1+ CD103- CD8+ T-cells. The lack of host B7-H1 results in compromised control of a heterologous virus re-challenge demonstrating a functional defect in TRM mediated virus control. This study reveals a new role for B7-H1 in TRM and pro-inflammatory PD-1+ CD103- CD8+ T-cell accumulation in the CNS and gives insight for using B7-H1/PD-1 blockade in modulating long-term T-cell protection.